Trends in extreme high temperature at different altitudes of Southwest China during 1961–2014 - Yuting XUE; Quanliang CHEN; Jiayu ZHANG; Ping HUANG (Atmospheric and Oceanic Science Letters, 2020)
This study analyzed the trends in extreme high temperature in Southwest China based on the observed daily maximum temperature and average temperature data from 410 Chinese stations recently released by the China Meteorological Administration. The authors found that the trends in extreme high temperature at different altitudes of Southwest China exhibit staged variations during a recent 50-year period (1961–2014). The trends in mean temperature and maximum temperature also exhibit phase variation. All temperature-related variables increase gently during the period 1975–94, whereas they increase dramatically during the recent period of 1995–2014, with a rate that is approximately two to ten times more than that during 1975–94. In addition, the trends in mean temperature, maximum temperature, and the frequency of extreme high temperature in the low altitudes transit from negative to positive in the two periods, while they increase dramatically in the mid- and high-altitude areas during 1995–2014, the well-known global warming hiatus period. In particular, the maximum temperature increases much faster than that of average temperature. This result implies that the regional temperature trend could be apparently different from the global mean temperature change.